Locating Postcolonial Locality through Children Literature in building Social Conflict Reconciliation - Winda Candra Hantari; Ali Imron (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2019)
This study aims to produce a nonformal literary learning model for children contribute to social conflict reconciliation which is acceptable and contains locality values in a postcolonial perspective. The perspective enables participants involved in this learning process to understand their role in (re) producing or changing discourse exposed in the learning process; to connect literacy with problem solving for conflict reconciliation, to connect content learned in non-formal academic situations with the current situation of the digital world in daily life exposed to global trends. The learning model was observed on residents affected by the relocation of the construction of the Yogyakarta International Airport consisting of 4 Villages. There are 16 samples which are elementary school age children, and 16 samples of their mothers. Sampling using a purposive random sampling technique. The data collection method uses the method of documentation, observation, and two questionnaires namely PK and KT series. Data analysis was qualitative using Cohen-Kappa coefficient analysis. The result shows that the procedure for developing informal literary learning model in 4 affected villages is able to produce appropriate and applicable mentoring models in accordance with 3 classifications namely literacy capital, knowledge of locality, and perception of otherness. The coefficient of inter-rater κ results from an evaluation of the accuracy of the model is 0.75 therefore it meets the level of feasibility model.